Assessment of physical and technical training level in basic specialization stage in women`s artistic gymnastics - Potop, V. (Journal of Physical Education and Sport, 2013)
The main goal of this paper is the assessment of the physical training influence on technical training in women`s artistic gymnastics throughout basic specialization stage. With this aim in view, we have considered that the assessment of physical and technical training level would highlight the extent to which this one affects performances achieved in competitions in terms of difficulty, execution and final score on apparatus. The study was conducted from September to December 2012 in the Juniors Olympic Team of Deva, with a group of 11 female gymnasts, 12 to 14 years old. This study refers to the ascertaining stage of a post doctoral research on the macro methods of gymnastics exercises learning throughout basic specialization stage in women`s artistic gymnastics. For this purpose, the following methods have been used: method of bibliographic study, method of observation, method of experiment, method of experts, statistical mathematical method and graphical representation method. In order to assess the level of basic physical and technical training of junior female gymnasts aged 12 to 14, control trials were applied for monitoring the muscular strength, sense of balance and basic technical level. The results of training level testing assess the level of development of arms, abdomen, back, lower limbs muscular strength, the level of explosive strength (flashing), combined strength and sense of balance. The results of basic technical training assessed using the experts` method point out the level of technical execution on each apparatus. The results achieved in competition highlight the scores for difficulty (D), execution (E) and final score (FS) on each apparatus. The assessment of physical and technical training shows the influence exerted by this one on the results achieved in competition in terms of difficulty, execution and final score on apparatus.